Improving Recovery Process of Omega-3 Fatty Acids from a Native Species of Chlorella vulgaris Using Integrated Method - Arabian, Daryush; Amiri, Peyvand (Applied Food Biotechnology, 2020)
Background and Objective: Fish tissue and liver and some microalgae are some of the richest sources of omega-3 (ω3) fatty acids in nature. Annually, more than 4.2 billion tons of algae are cultivated with various goals. Therefore, development of novel ways to extract more ω3-fatty acids from microalgal tissues is a valuable target. In this study, comparisons were carried out between various methods of extraction and purification of ω3-fatty acids from a native species of microalgae. Material and Methods: Combination method (urea complex and winterization) used as a method for extraction of ω3-fatty acids. For the optimization of combination method, three factors, including temperature of winterization, time of winterization and frequency of extraction with hexane were studied at four various levels and 15 examinations using Design Expert 10.0 software. Results and Conclusion: Results of optimization included 10 h for time of winterization, -20 °C for temperature of winterization and six times of extraction with hexane. In optimized conditions, the highest quantity of ω3-fatty acids derived from Chlorella vulgaris at the moisture of 65% was 43.6 mg g-1 fatty acids.